2014
DOI: 10.1089/cyber.2013.0481
|View full text |Cite
|
Sign up to set email alerts
|

Game-Based Digital Interventions for Depression Therapy: A Systematic Review and Meta-Analysis

Abstract: The aim of this study was to review the existing literature on game-based digital interventions for depression systematically and examine their effectiveness through a meta-analysis of randomized controlled trials (RCTs). Database searching was conducted using specific search terms and inclusion criteria. A standard meta-analysis was also conducted of available RCT studies with a random effects model. The standard mean difference (Cohen's d) was used to calculate the effect size of each study. Nineteen studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
129
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(139 citation statements)
references
References 44 publications
4
129
0
6
Order By: Relevance
“…Two reviews (9, 32) examined serious games for depression, while Li et al (31) focused specifically on a subset of serious games, exergames. Fleming et al (9) identified nine studies of six computerized interventions that utilized gaming as a major or primary component to treat or prevent depression.…”
Section: Existing Research: a Scoping Reviewmentioning
confidence: 99%
“…Two reviews (9, 32) examined serious games for depression, while Li et al (31) focused specifically on a subset of serious games, exergames. Fleming et al (9) identified nine studies of six computerized interventions that utilized gaming as a major or primary component to treat or prevent depression.…”
Section: Existing Research: a Scoping Reviewmentioning
confidence: 99%
“…This evaluation addresses a unique combination of setting, patient and intervention characteristics (mindfulness approach and blended mode of supply). Achieving the predetermined required sample size for observing a modest effect with reasonable chance responds to previous reviews on the effectiveness of games for health that found promising results of mainly small, underpowered, studies [35,40]. Furthermore, this study has taken account of Type I error risk through outcome multiplicity, factors of non-usage, and risk of biased patient expectations through the informed consent procedure.…”
Section: Strengths and Limitationsmentioning
confidence: 83%
“…It was previously hypothesized that behavioral change is strengthened by engagement qualities triggered by storytelling, fantasy, and interactivity in serious games [34]. In the fields of mental health care and rehabilitation, gaming, motion capturing, and virtual reality technologies may support treatment effectiveness for various wellknown conditions such as depression, anxiety, phobias, post-stroke, and acute pain [39][40][41][42]. Adequately powered studies on the effects of games for health are lacking in general, and little to nothing is known about complementary effectiveness in regular health care contexts, such as multidisciplinary rehabilitation [43].…”
Section: Why Serious Games May Offer a Potential Solutionmentioning
confidence: 99%
“…The community for research on video games for assessment and intervention for mental health spans multiple disciplines, from cognitive sciences, computer science, and interaction design, to psychology, neurobiology, and medicine [24]. The goal of this workshop is to bring together an international group of researchers to discuss the current state of games for mental and formulate a plan for moving this research agenda forward in the CHI PLAY community.…”
Section: Games For Mental Healthmentioning
confidence: 99%